TEACHER TRAINING FOR CITIZENSHIP IN CONTEXTS OF NEOLIBERALISM: PROPOSALS FROM THE NARRATIVES - Marta Susana Bertolini (Universidad Nacional del Nordeste, 2019)
Neoliberal policies expanded globally affect the exercise of rights and full citizenship. The Research Project of which this work is part, seeks to understand the ways in which the students of the initial education teachers live the political, situations that they recover from their school biography and their life stories, in order to make them visible and analyze the contexts of production, from the awareness and reflexivity, to recognize themselves as active subjects in the construction of their own subjectivity and in the construction of the world they inhabit, in their social, economic, political and cultural dimensions, that is, to position themselves as active subjects of politics. By relating our own experience, through the narrative, it is possible to visualize the constitution of our own subjectivity and to become aware of the worlds that inhabit us, distinguishing different techniques of domination. Experiences, these, indispensable to make pedagogical proposals in which, from the first months of life, boys and girls are real participants in socialization processes that are identified as emancipatory.